The Transformation of Balinese Satua Values: Strengthening the Character Education of the Alpha Generation: (A Case study at Saraswati Tabanan Kindergarten, Bali) - Adhi, Made Kerta; Parmini, Ni Putu; Wulandari, Ni Putu Desi (Jurnal Ilmiah Peuradeun, 2020)
The study aims at describing the transformation of the Balinese satua values for strengthening the alpha generation (Gen A)’s character education in Kindergarten Saraswati Tabanan. The method used was qualitative research with a Cultural Studies approach. The results showed that Masatua (storytelling) was carried out for twenty minutes every “Thursday Cultures" in Balinese, such as Masatua Siap Selem, and Ni Bawang Teken Ni Kesuna. They were very happy to listen to stories because they were supported by pictures media, the narrator were hilarious and familiar, interspersed with dialogues and Balinese folk songs. Previously, the characters of the Gen A was relatively less independent or less confident, spoiled, and egocentric. After Gen A were given Balinese storytelling continuously, there were process internalization of balinese satua values, which can influence the strengthening of the character of children, such as children become independent, confident, religious, honest, disciplined, tolerant, creative, and responsible. In conclusion, the Balinese satua contains noble moral values that can be told to children with practical ways, and pragmatic manner in a pleasant atmosphere. Masatua was carried out sustainable so that it became a habit, culture and can strengthen the characters of Gen A, and also preservation and development of local wisdom.